Keterampilan Berpikir yang Dibangun dalam Pengajaran di Perguruan Tinggi Islam: Survey di STIT Raden Wijaya Mojokerto - Hariris Nurcahyo (PROGRESSA: Journal of Islamic Religious Instruction, 2019)
Education must consist of more than an accumulation of unreasonable facts and skills, and that modern society demands a highly developed critical awareness to overcome its increasing complexity. The purpose of teaching a subject is to teach the contents of the subject, not to teach thinking. We are all students in elementary and secondary schools. How long does our teacher offer for teaching thought? The purpose of this study is to describe and analyze the thinking skills that are built in teaching in Islamic universities: survey at STIT Raden Wijaya Mojokerto. from the results of the analysis concluded: Teaching at Islamic universities (STIT Raden Wijaya Mojokerto) skills built by lecturers is 75% based on LOTS-Lower Order Thinking Skill. And 25% are based on HOTS-Higher Order Thinking Skill